In vitro anticoccidial activity of Vitis vinifera extract on oocysts of different Eimeria species of Broiler Chicken - ABBAS, R.Z.; ABBAS, A.; IQBAL, Z.; RAZA, M.A.; HUSSAIN, K.; AHMED, T.; SHAFI, M.U. (Journal of the Hellenic Veterinary Medical Society, 2020)
In the current experiment, the in vitro anticoccidial effect of Vitis venifera (grape seed) extract was evaluated. For this purpose, an in vitro sporulation inhbition assay was used. Collected oocysts of four Eimeria species (E. tenella, E. necatrix, E. brunetti and E. mitis) were exposed to six different concentrations (w/v) of Vitis vinifera extract (VVE) in 10% Dimethylsulphoxide solution (DMSO), while Dimethylsulphoxide (DMSO) and Potassium dichromate solution (K2Cr2O7) served as control groups. The results of the present study revealed that V. vinifera extract showed inhibitory effect on sporulation (%) and damage (%) of Eimeria oocysts in a dose dependent manner as compared to both control groups. V. vinifera extract also damaged the morhology of oocysts in terms of shape, size and number of sporocysts.